2011
DOI: 10.1038/nature10426
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of human adipose lipid turnover in health and metabolic disease

Abstract: Adipose tissue mass is determined by the storage and removal of triglycerides in adipocytes. Little is known, however, about adipose lipid turnover in humans in health and pathology. To study this in vivo, lipid age was determined by measuring nuclear bomb test-derived 14C in adipocyte lipids. We report that during the average ten year life span of human adipocytes, triglycerides are renewed six times. Lipid age is independent of adipocyte size, is very stable across a wide range of adult ages and does not dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
309
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(324 citation statements)
references
References 22 publications
10
309
2
3
Order By: Relevance
“…The observation that SEMA3C expression correlated significantly with adipocyte morphology (a measure that is independent of body fat mass as discussed [18]) demonstrates that there is a link between relative fat-cell size and SEMA3C levels. Fat-cell morphology is determined by adipocyte [18] and lipid turnover [44]. However, the transcriptional networks that regulate these processes have not yet been determined and their potential role in regulating SEMA3C requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that SEMA3C expression correlated significantly with adipocyte morphology (a measure that is independent of body fat mass as discussed [18]) demonstrates that there is a link between relative fat-cell size and SEMA3C levels. Fat-cell morphology is determined by adipocyte [18] and lipid turnover [44]. However, the transcriptional networks that regulate these processes have not yet been determined and their potential role in regulating SEMA3C requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Lipolysis in white adipose tissue, the cleavage of triglycerides and the release of fatty acids and glycerol play essential roles not only in lipid and energy homeostasis [26] but also in the development of lipotoxicity and fat redistribution [27,28] . Here, we have shown that lipolysis is enhanced in the visceral white adipose tissue in a rat model of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…At age 50, 55% of human cardiomyocytes remain from birth and over the first decade of life, cardiomyocytes often undergo a final round of DNA synthesis and nuclear division without cell division, resulting in ~25% of human cardiomyocytes being binucleated [19]. Similarly, the average lifespan of human adipocytes is ~10 years and the number of fat cells in adult humans remains quite constant with an annual turnover rate of only ~10% [20,21]. The post-mitotic nature of terminally differentiated cells would suggest that dedifferentiation, a process thought to be genetically regulated [22,23] in which a specialized cell takes on a more primitive state, although representing one potential aspect of plasticity in the stem cell progeny, may not take place prevalently under homeostatic conditions in adult mammalian organs ( Figure 3A).…”
Section: Plasticity Of Normal Stem Cell Progenymentioning
confidence: 99%